Digital Financial Compliance Challenges: Applying Routine Activity Theory to Online Gambling Networks Analysis - Rizal Mawardi; Vira Nuraeni; Jasman Jasman; Huda Trihatmoko; Fangky A. Sorongan; Septian Aripin; Syaefulloh Maulana Malik (Emerging Science Journal, 2026)
This study examines Indonesia's Financial Intelligence Unit (INTRAC) "follow the money" investigative techniques through Routine Activity Theory, analyzing criminal convergence in online gambling money laundering operations. Using qualitative methodology with interviews, observation, and document analysis (December 13-19, 2024), the research applied Cohen and Felson's framework to understand criminal patterns in digital financial ecosystems. Data analysis using Audit Command Language (ACL) revealed criminal convergence patterns where motivated offenders (84.63% male, 50% private sector employees, 53% aged 20-30) exploited digital infrastructure vulnerabilities. Sophisticated schemes included multiple nominee accounts, 5-8 layered transactions, and cryptocurrency laundering in low-surveillance environments. Transaction analysis showed expanding criminal opportunities, increasing to IDR 691.88 trillion (2017-2024). The study demonstrates how digital transformation creates suitable targets faster than regulatory adaptation. Research contributes theoretical insights explaining financial irregularity patterns through routine activity theory while offering practical risk reduction models for global financial intelligence units, advancing regulatory compliance theory and digital financial risk prevention.